Acute effects of stretching on maximal muscle strength and functional performance: A systematic review of Japanese-language randomised controlled trials. (February 2016) - Mine, Koya; Nakayama, Takashi; Milanese, Steve; Grimmer, Karen
Abstract: Background: There is no consensus in the English-language literature regarding the best types or dosages of stretching to maximise muscle strength and functional performance. It is possible that primary research published in non-English languages provides different insights, and could add to the body of international knowledge. Purpose: This systematic review aimed to identify and evaluate Japanese-language randomised controlled trials (RCTs) investigating acute effects of stretching on maximal strength and functional performance. Methods: Three Japanese databases and five English databases were searched from inception to 24 March 2015. Only Japanese-language RCTs examining acute effects of stretching on maximal strength and/or functional performance were included. Risk of bias in included studies was assessed using Physiotherapy Evidence Database scale. GRADE (Grading of Recommendation Assessment, Development and Evaluation) approach was applied to evaluate the quality of evidence. Descriptive synthesis was attempted. Results: Seven RCTs with variable methodological quality were included. No two studies were the same, thus meta-analysis was not possible. Descriptively, because of heterogeneity of interventions and outcome measures, it was not possible to identify consensus on the benefits of stretching. GRADE approach indicated low to very low quality evidence for this topic. Conclusion: This review of Japanese-language RCTs provided no additional information to strengthen or challenge the current English-language evidence base on acute effects of stretching on maximal strength and performance. Future Japanese-language studies should address methodological flaws exposed in this review and incorporate functional outcome measures to strengthen the international evidence base. Highlights: Seven Japanese-language RCTs met the eligibility criteria and were included. Methodological quality was varied, ranging from 4 to 7 in PEDro scale. Meta-analysis was impossible due to heterogeneity in the included studies. Based on GRADE approach, 11 comparisons showed very low to low quality evidence. This review did not strengthen or challenge the current evidence base.